STRATEGI GENERIK PORTER BAGI UMKM DALAM MENGHADAPI MASYARAKAT EKONOMI ASEAN (MEA) (Studi Kasus: Pada UMKM Di Kabupaten Deli Serdang) - Julita, Julita; Sari, Eka Nurmala (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2015)
This study aims to find out the problems that often hinder the development of SMEs in Deli Serdang in competitive advantage, especially in the face of the MEA, it is necessary for a strategy for creating a competitive advantage in the era of the MEA. Many strategies to create competitive advantage and one generic strategy Porter. This strategy gives success in the company so that the researcher wants to adoption Porter generic strategies for SMEs, especially in Deli Serdang The object of this research is the small and medium-sized businesses (SMEs) in Deli Serdang. Data collection techniques using questionnaires and interviews / structured interviews and data analysis techniques using descriptive analysis techniques. The results showed that the strategy porter through indicators five forces porter which includes competition among similar companies, the threat of new entrants, threat of substitute products, bargaining power of buyers and the bargaining power of suppliers is still included in the category enough or moderate, indicating the presence of obstacles or problems faced by SMEs in Deli Serdang. Besides the five forces porter indicator, additional supporting indicators such as innovation and technological capabilities as well as the governments attention is also included in the category enough or moderate, indicating that the supporting indicators are still facing obstacles or problems